Book Review:ANDREAS K. DEMETRIADES (ed.), Iatrosophikón. Folklore Remedies from a Cyprus Monastery: Original text and parallel translation of Codex Machairas A.18, Foundation Anastasios G. Leventis, Nicosia 2015, lx+654 pp. ISBN 978-9963-732-15-9 - BOURAS-VALLIANATOS, Petros (Byzantina Symmeikta, 2018)
Book Review: Andreas K. Demetriades (ed.), Iatrosophikón. Folklore Remedies from a Cyprus Monastery: Original text and parallel translation of Codex Machairas A.18, Foundation Anastasios G. Leventis, Nicosia 2015, lx+654 pp. ISBN 978-9963-732-15-9